Functional Outcome of Mesenchymal Stem Cells Vs. Hyaluronic Acid in Knee Osteoarthritis Kellgren-Lawrence Grade I-III At 6-and 12-Months Follow-Up: A Meta-Analysis - I Gusti Ngurah Wien Aryana; Febyan; Shianita Limena (Journal Orthopaedi and Traumatology Surabaya, 2023)
Background: Osteoarthritis (OA) is a degenerative synovial joint disease with progressive pain and deformity. Stem cell therapy, especially mesenchymal stem cells (MSCs), has revolutionized the treatment of knee OA. However, clinical evidence for MSCs in the treatment of knee OA is insufficient. The primary objective of this research is to offer substantiation and recommendations for advancing and utilizing MSC therapy in clinical settings, in contrast to the use of hyaluronic acid (HA) as the standard control group.Methods: This study was a meta-analysis conducted through a search for relevant scientific reports in PubMed, Embase, and Google Scholar, using some keywords such as "mesenchymal stem cell," "hyaluronic acid," and "osteoarthritis." Results: Mesenchymal stem cells showed promising results on a clinical basis. Among five included studies of 139 patients with knee osteoarthritis consisting of 70 patients treated with MSC and 69 patients treated with HA, mesenchymal stem cells provide significant short-term pain relief at 6- (I2=34%; SMD=-0.58 95% CI, -1.09 to -0.07; p=0.02) and 12-months follow-up (I2=28%; SMD=-0.79 95% CI, -1.22 to -0.37; p=0.0003), with relative clinical improvement. The highly differentiated MSC aids in tissue repair, regulation of immune response, and anti-inflammatory effect on knee osteoarthritis, including the chondrogenesis mechanism.Conclusion: Mesenchymal stem cell therapy has shown effectiveness compared to hyaluronic acid injection for knee osteoarthritis, providing pain relief and improved functional outcomes on short-term intervals up to 12 months follow-up. Mesenchymal stem cells display some chondroprotective effects requiring further research and development.